Identifying Factors that Contribute to the Social Responsibility of Young People and Some Suggestions for Promoting Social Responsibility of Vietnamese Youth Today - Van Kim, Nguyen; Thi Hai Yen, Hoang (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4388, 2022)
Youth is a social class that contributes significantly to national strength and is one of the factors determining the country's future. Throughout Vietnamese history, youth have always served as the strike force in the cause of national construction and defense. Youth is also an important factor in developing political-military strength, socioeconomic development, and cultural creativity. In the context of globalization and a dynamic society such as Vietnam today, young people are emerging as a source of "knowledge" labor and the country's creative subject. Our Party and State have always placed a high value on youth development work, with a particular emphasis on the social responsibility of Vietnamese youth. Whether or not the Doi Moi is successful, whether or not the country enters the twenty-first century with a worthy position in the world community, and whether or not the Vietnamese revolution firmly follows the socialist path depends largely on the youth force, on fostering and training the young generation". Article 4 of the Law on Youth (2020) states unequivocally: "Youth are a great social force, who is impulsive and creative, leading the process of renewal, construction, and defense of the Vietnamese Fatherland and society" tenet; play an important role in the country's industrialization and modernization, international integration, and socialism building". Therefore, along with the rights and obligations of citizens according to the provisions of the Constitution and the law, it is also important to promote the social responsibility of the youth. A research that clarifies the concept and characteristics of social responsibility of youth in the current context is meaningful in orienting the youth social responsibility framework and is the foundation for proposing solutions to encourage young people to demonstrate their social responsibility. This article focuses on analyzing the concept of young people's social responsibility and the elements constituting social responsibility of young people.